The Impact of the Existence of a Ferry Port on the Socio-Economy of the Community in Gampong Teungoh, Samatiga District, West Aceh Regency - Mice Putri Afriyani; M. Fadjar Maulana (Seutia Hukamaa Cendekia, 2023)
The port is one of a country's most important transportation infrastructures, especially in a maritime country like Indonesia. Ports can help improve the country's economy; with a port, a country's economic activities will be smoother. The existence of a port, this is also related to regional development. In essence, regional development is an effort to add value to what is owned by an area to improve the quality of life and increase the wealth of an area. The purpose of this research is to find out the impact of the existence of the Ferry Port on the economic development of the community in Gampong Teungoh, Samatiga District, West Aceh Regency. This study used a descriptive qualitative method. The population in this study is the entire community of Gampong Teungoh, totalling 186 families, with a sample of 20%, namely 37.2 or the same as 37 respondents. Collecting data in this study using a questionnaire with scale Guttman, then analyzed through simple statistical analysis. Based on the results of the data analysis, it can be seen that respondents answered